A COMPARATIVE STUDY OF ANTIMICROBIAL PROFILE HAVING BROAD SPECTRUM BACTERIOCINS AGAINST ANTIBIOTICS - Imran, Sabiha; Gupta, Twinkle; Arora, Aarti; Das, Nilanjan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Bacteriocins are ribosomally synthesized antimicrobial peptides produced by microbes owned by different eubacterial taxonomic branches. Most of them are small cationic membrane-active compounds that form pores in the targeted cells, disrupting membrane possibilities, and triggering cell fatality. The availability of small cationic peptides with antimicrobial activity is a protection strategy found not only in bacteria but also in plants and animals. The antibiotics which have extensive applications in the treatment of various bacterial diseases have developed alarming resistance against them in many pathogens due to improper use besides this antibiotics have adverse side effects also. There are an extensive variety of bacteriocins made by different bacterial genera have promising alternative to antibiotics that needs to be further studied to show the no existence of undesirable effects, which must be performed both in vitro and in vivo experimental systems. Most of the bacteriocin have narrow spectrum of their activity and effective only on the related species. There is an urgent need for the identification of broad-spectrum bacteriocins isolated from the species from different habitats that can be effective against both Gram-positive and Gram-negative pathogens. In this review, we focus on the main physical and chemical characteristics of broad-spectrum bacteriocin and discuss their application as an alternative option to antibiotics.